A long non-coding RNA with important roles in the carcinogenesis - Ghafouri-Fard, Soudeh; Askari, Arian; Hussen, Bashdar Mahmud; Taheri, Mohammad; Mokhtari, Majid (Frontiers in Cell and Developmental Biology, 2022)
Long non-coding RNAs are demonstrated to contribute to carcinogenesis. TMPO Antisense RNA 1 (TMPO-AS1) is an example of lncRNAs with crucial roles in this process. This lncRNA serves as a sponge for miR-320a, miR-383-5p, miR-329-3p, miR-126, miR-329, miR‐199a‐5p, miR-577, miR-4731-5p, miR-140-5p, miR-1179, miR-143-3p, miR-326, miR-383-5p, let-7c-5p, let-7g-5p, miR-199a-5p, miR-200c, miR-204-3p, miR-126-5p, miR-383-5p, miR-498, miR-143-3p, miR-98-5p, miR-140 and miR-143. It can also affect activity of PI3K/Akt/mTOR pathway. The current review summarizes the role of TMPO-AS1 in the carcinogenesis and assessment of its potential as a marker for certain types of cancers.